A CONCEPTUAL FRAMEWORK OF LAW AND SOCIAL CHANGE - Shelke, Sagar Vilas (International Journal of Psychosocial Rehabilitation, 2020)
Law is framed as the standards and rules to be followed for the peaceful living of the people in the society , while social change is the alteration in the society which may have either good or bad impact in the society.The relationship between the law and social change is discussed at a wider aspect. There are various mechanisms being used by the legislation to implement the rules in the society. It focuses on the way that the law has been implemented and its responses or the effects in the society. Generally they put forth the question that whether every law that had been enacted has brought only the good effect and whether the protection of the country has been a great concern for the legislation.